Walter Mondale for President Rally at Farmer's Market at Divisadero and Tulare - Watkins, Howard::::::::: (1984)
Annie Van Patten and Jake Tilley waving at camera "Viva Mondale", "Mondale the Women's Choice", Mondale-Ferrero: Action Not Acting", "Fresno Loves Fritz and Ferrero"